In Memoriam Carlos Javier Echarri Cánovas - Cárdenas, Rosario; Giorguli, Silvia E.; Pacheco, Edith (El Colegio de México A.C., 2019)
A few days ago, the unexpected death of Carlos Echarri moved communities of scholars in both the Mexican and the international population. Carlos Echarri was a research fellow at the Center for Demographic, Urban and Environmental Studies of El Colegio de México, an institution where he held the position of coordinator of the Master’s Degree Program in Demography and the Doctoral Program in Population Studies. He also coordinated the Reproductive Health and Society Program. In his many roles at El Colegio de México. In December 2018, he was appointed director of the National Population Council. Despite his short time at the Council, Carlos Echarri left an unquestionable mark, and was portrayed as an “exemplary official who promoted several initiatives for the benefit of citizens, and the agenda of Human Rights and freedoms in population policies”.